Water mite species of the genus Hydrodroma Koch (Acari: Hydrachnidia, Hydrodromidae) from Australasia. Part I - Pesic, Vladimir; Smit, Harry (Zootaxa, 2007)
Three new water mite species of the genus Hydrodroma Koch (Acari: Hydrachnidia, Hydrodromidae), characterized by more than one swimming setae on II-L-5, are reported from Australia and New Caledonia: Hydrodroma kununurra sp. nov., H. australis sp. nov. and H. kakadu sp. nov.